Risk factors for complications after ileocolonic resection for Crohn’s disease with a major focus on the impact of preoperative immunosuppressive and biologic therapy: A retrospective international multicentre study - Yamamoto, Takayuki (2016)
Background: In the era of biologic agents, risk factors for complications following resection for Crohn’s disease have not been fully identified. In particular, the association of preoperative use of immunosuppressive and biologic agents with the incidence of complications after resection remains to be elucidated. Author note: TY, AS, YS, FVT and PGK designed the study. All authors did data collection and gave scientific contribution to the study design and discussion. TY, AS and PGK drafted the article. All authors read and approved the final version of the manuscript. Aim: This retrospective multicentre study aimed to identify risk factors for complications after ileocolonic resection for Crohn’s disease, with a major focus on the impact of preoperative immunosuppressive and biologic therapy. Methods: A total of 231 consecutive patients who underwent ileocolonic resections for active Crohn’s disease in seven inflammatory bowel disease referral centres from three countries (Japan, Brazil and Italy) were included. The following variables were investigated as potential risk factors: age at surgery, gender, behaviour of Crohn’s disease (perforating vs. non-perforating disease), smoking, preoperative use (within eight weeks before surgery) of steroids, immunosuppressants and biologic agents, previous resection, blood transfusion, surgical procedure (open vs. laparoscopic approach), and type of anastomosis (side-to-side vs. end-to-end). Postoperative complications occurring within 30 days after surgery were recorded. Results: The rates of overall complications, intra-abdominal sepsis, and anastomotic leak were 24%, 12% and 8%, respectively. Neither immunosuppressive nor biologic therapy prior to surgery was significantly associated with the incidence of overall complications, intra-abdominal sepsis or anastomotic leak. In multivariate analysis, blood transfusion, perforating disease and previous resection were significant risk factors for overall complications (odds ratio [OR] 3.02, 95% confidence interval [CI] 1.21–7.52; P = 0.02), intra-abdominal sepsis (OR 2.67, 95% CI 1.04–6.86; P = 0.04) and anastomotic leak (OR 2.87, 95% CI 1.01–8.18; P = 0.048), respectively. Conclusions: Blood transfusion, perforating disease and previous resection were significant risk factors for overall complications, intra-abdominal sepsis and anastomotic leak after ileocolonic resection for Crohn’s disease, respectively. Preoperative immunosuppressive or biologic therapy did not increase the risk of postoperative complications.